2009
DOI: 10.4137/aswr.s1004
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Element Concentrations in Vegetables Cultivated in Acidic Compared to Alkaline Areas of South Sweden

Abstract: A study in 1997, on mineral levels in acidic compared to alkaline well waters, and in women's hair, revealed higher concentrations of a number of mineral elements like Ca, Mo and Se in alkaline waters and hair. Thus, median Ca levels were six times higher in well water and fi ve times higher in hair from the alkaline area compared to the acidic area. This fi nding raised the probability of similar differences in vegetables from these areas. Thus, in the year 2006, 60 women who had participated in the study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
2
2
Order By: Relevance
“…Our results agree with those reported by Demirezen and Aksoy (2006), Kachenko and Singh (2006), Prabu (2009) and Akan (2009). Previous studies carried out by other researchers (Eslami et al 2007, Yargholi et al 2008, Lacatusu et al 2008, Kumar et al 2009, Rosborg et al 2009 show that Cd were found higher than our results. Cd is accepted as a first-degree carcinogenic material.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with those reported by Demirezen and Aksoy (2006), Kachenko and Singh (2006), Prabu (2009) and Akan (2009). Previous studies carried out by other researchers (Eslami et al 2007, Yargholi et al 2008, Lacatusu et al 2008, Kumar et al 2009, Rosborg et al 2009 show that Cd were found higher than our results. Cd is accepted as a first-degree carcinogenic material.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the concentration of Cu in leaves was the same as reported by (Kachenko and Singh 2006, Akan et al 2009and Rosborg et al 2009. The studies performed by (Raza 2005, Lacatusu et al 2008, Cheraghi et al 2009, Prabu 2009 show that concentrations of Cu were higher than the values obtained in this study.…”
Section: Resultssupporting
confidence: 88%
“…The concentrations of Cr detected in the vegetable samples ranged from 0.23 to 3.22 mg/kg; 0.23 to 3.43 mg/kg Mn; 0.23 to 3.45 mg/kg Fe; 0.21 to B 3.54 mg/kg Ni; 0.25 to 4.56 mg/kg Pb; 0.87 to 8.34 mg/kg Zn; 0.34 to 5.44 mg/kg Cd and 0.21 to 3.22 mg/kg Cu. Previous studies carried out by other researchers (Kumar et al, 2009;Rosborg et al, 2009) show that Cd were found higher than our results. Our results are also in conformity with Delbari and Kulkarni (2013) who reported maximum Cd, Pb and Fe were observed in spinach.…”
Section: Nickelcontrasting
confidence: 76%
“…Specifically, the high Al (up to 350 mg/kg) in the plant samples is indicative of soil particulate rather than physiological metals (Rosborg et al 2009), and Pb is a co-contaminant associated with these particles. Al is not taken up to a significant degree by plants except at quite low soil pH, so that physiological Al in leafy vegetables is typically no greater than 10-20 mg/kg (Pillay and Jonnalagadda 2007).…”
Section: Resultsmentioning
confidence: 99%